Strategi Organisasi Dalam Meningkatkan Prestasi ( Akademik dan Non-Akademik) Mahasiswa - Arumdani, Alya Leci (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
In the era of globalization, universities are required not only to produce graduates who excel academically but also to equip them with non-academic skills relevant to societal and workforce demands. Student organizations serve as platforms for character building, intellectual capacity development, and soft skills training that support students’ overall success. The aim of this study is to describe the organizational strategies of student bodies, particularly the Student Executive Board (BEM) of Universitas Negeri Surabaya, in enhancing students’ academic and non-academic achievements through Heinrich Pestalozzi’s holistic education approach. This research employed a qualitative method using in-depth interviews, observation, and documentation to obtain comprehensive data. The findings reveal that BEM UNESA’s strategies include strengthening academic capacity through seminars and study communities, fostering leadership through social engagement, and utilizing digital technology in organizational management. These strategies align with Pestalozzi’s principles emphasizing the balance of head (intellect), heart (emotion), and hand (practical skills). The study indicates that students’ active participation in organizations not only positively influences academic achievement but also enhances soft skills, social awareness, and leadership character. Thus, student organizations are proven to be strategic avenues for shaping competent, adaptive, and character-driven young generations in the global era.